Multifaceted impacts of double-aging neighborhood’s built environments on SAIP: a deep dive into Chinese rapidly aging urban society - Yue Qian; Guanmin Qiao; Guanmin Qiao; Guanmin Qiao; Guoping Zhang; Xianjing He; Renfeng Ma; Renfeng Ma; Renfeng Ma (Frontiers in Public Health)
IntroductionThe healthy aging of older adults in dual-older adult communities is influenced by multiple factors, and understanding its underlying mechanisms can promote healthy aging among the older adults in a wide range of developing countries. This comprehensive study delves into the intricate interplay between multifaceted built environmental factors, and their direct and indirect effects on the successful AIP residing in double-aging neighborhoods.MethodsApplying a series of HLM, the research meticulously explores the intricate links between SAIP and multi-scale aging spaces, including home space, community social participation, and built environments.ResultsThe results show that: (1) Older adults people’s need for spiritual comfort derived from home space exceed the need for financial support and family care, becoming a major positive factor for SAIP; (2) The neighborhood based on acquaintance society, partly replace the role of home-based care in influencing SAIP. Especially, community participation has a positive impact, serving as an extension of the home space, such as college for senior citizens and outdoor activity space; (3) The built environment of double-aging neighborhoods has a significant positive effect, with a sense of place identity replacing the reliance on family members and acquaintances to facilitate SAIP; (4) In high-density old district, the distribution of public facilities is saturated, and the proper utilizes of these facilities becomes an important factor affecting SAIP.DiscussionWe provide a multi-factorial perspective of SAIP, demonstrating the compensatory and substitutional roles of community-based older adults care services and friendly neighborhood relationships in fulfilling home-based older adults care functions. This approach better promotes the construction of age-friendly communities and supports SAIP.